A device to simulate contaminant transfer and surface and subsurface flow through intact soil monoliths. Issue 2 (23rd February 2022) - Hachgenei, Nico; Nord, Guillaume; Spadini, Lorenzo; Mora, Henri; Courvoisier, François; Sutra, Jean‐François; Vandervaere, Jean‐Pierre; Legoût, Cédric; Morel, Marie‐Christine; Martins, Jean; Lespine, Anne; Duwig, Celine
Abstract: Many contaminants of agricultural origin are released into rural environments, particularly at the soil surface. Their fate has been extensively investigated in repacked soils, but only few studies have addressed their transport in structurally preserved natural soils. Much remains unknown about their fate and transfer within and between environmental compartments, while the susceptibility of these compartments to the contaminants adverse effects can vary considerably. The lack of studies regarding surface and subsurface transfer of contaminants through intact soil compared with studies on repacked soil led us to propose a device and protocol for sampling intact soil monoliths (60 × 30 × 22 cm 3, length, width, depth [LWD]) without heavy machinery. This is achieved by a modular design with removable top and bottom lid and a protocol of cutting the soil and replacing the affected bottom soil with a drainage layer of glass beads. The device allows the application of artificial rainfall events with simultaneous highly resolved quantification of infiltration excess overland flow and drainage discharge. It is designed to facilitate the collection of samples for physical, biological, and chemical analyses that fulfill cleanliness standards for organic contaminant analysis at trace levels using only poorly reactive stainless steel and glass materials. Testing of the device was performed by measuring the transfer of the antiparasitic drug ivermectin (IVM) through and over a silt‐loam pasture soil. This test case illustrates how the device can be used to gain valuable information on the transfer of trace organic contaminants through topsoils. Core Ideas: A device for collecting intact soil and subjecting it to artificial rainfall was developed. The setup allows for high resolution measurement and sampling of drainage and overland flow. It is designed for clean sampling permitting analysis of various contaminants at trace levels. We present an experiment to test the device on transfer of ivermectin from cow dung.